2021
DOI: 10.1093/sysbio/syab007
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Series and Size: Clade-Wide Investigation of Molar Proportions Reveals a Major Evolutionary Allometry in the Dentition of Placental Mammals

Abstract: Iterative segments such as teeth or limbs are a widespread characteristic of living organisms. While their proportions may be governed by similar developmental rules in vertebrates, there is no emerging pattern as regards their relation to size. Placental mammals span eight orders of magnitude in body size and show a wide spectrum of dietary habits associated with size and reflected in their dentitions, especially molars. Although variation in size constitutes an important determinant for variation in biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…We found that 3P3ML bats seem to exhibit higher rates of cell division in the premolar area compared to species with other morphotypes, while 2P3MS and 2P2MS bats tend to show the lowest rates of cell division. These results echo previous results in long-jawed nectarivorous noctilionoids 14 and support the idea that differences in cell proliferation or growth rate contribute to and possibly drive craniofacial 15 and tooth size 18 differences between species (Fig. 4D).…”
Section: The Number and Proportion Of Premolars And Molars Is Associa...supporting
confidence: 91%
See 2 more Smart Citations
“…We found that 3P3ML bats seem to exhibit higher rates of cell division in the premolar area compared to species with other morphotypes, while 2P3MS and 2P2MS bats tend to show the lowest rates of cell division. These results echo previous results in long-jawed nectarivorous noctilionoids 14 and support the idea that differences in cell proliferation or growth rate contribute to and possibly drive craniofacial 15 and tooth size 18 differences between species (Fig. 4D).…”
Section: The Number and Proportion Of Premolars And Molars Is Associa...supporting
confidence: 91%
“…However, little is known about how this diversification could be facilitated by the developmental mechanisms controlling tooth development. In particular, molar development and proportions have been shown to be constrained in mammals through the IC [16][17][18]42 , making it traditionally difficult to explain the colonization of new morphospaces. While the expansion of studies to include more clades has revealed that some seemingly do not follow the expectations of the IC model 19,21,22,42 , the mechanisms by which these species escape this developmental bias remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated new trees using the nni function of the package "phangorn" (Schliep, 2011) and computed PGLS with these rearranged trees to estimate the ranges of R² and p-values. It should be noted that the R² value of a PGLS can hardly be compared with that of an ordinary least squares regression (Ives, 2019;Billet & Bardin, 2021). Consequently, our interpretations of data will rely as little as possible on these R² values alone.…”
Section: Body Mass Centroid Size and Gracility Indexmentioning
confidence: 99%
“…We represented diet in three dimensions (guild, composition and breadth) and tested how dental morphology is related to each parameter. Considering the repeated evolution of various noctilionoid lineages to occupy the same dietary guilds, we hypothesised that 1) bat dental morphology does not have strong phylogenetic structuring; 2) noctilionoid bats show a significant allometric effect on dental morphology, following a general mammalian pattern in molar size (Billet & Bardin, 2021); 3) topographic complexity increases in guilds representing biomechanically demanding diets (i.e. frugivory and animalivory); and 4) dietary composition will reveal patterns of variation in the DTA metrics that reflect the level of intensity with which species exploit different food items.…”
Section: Introductionmentioning
confidence: 99%